Temperature profile in a 700m bore-hole at Mizuho Station, East Antarctica - Fumio Okuhira; Fumihiko Nishio; Kouichi Ikegami (National Institute of Polar Research, 1988)
A temperature profile was measured with a wall contact-type thermister probe in a 700m bore-hole at Mizuho Station, Antarctica. The temperature rapidly decreased from the snow surface to the 100m deep layer and slowly decreased toward deeper layers. It was the lowest (-35.48℃) at about 350m depth and it gradually increased with depth. The temperature profile measured could be suggested to differ from the condition of ice sheet predicted by the theoretical calculation.